Friction scince and technology - Blau, Peter J (Mechanical engineering (Marcel Dekker, Inc.), 1996)
"Exploring the rudimentary lubrication concepts employing solids, liquids, and grease, Friction Science and Technology describes material-based treatments of friction...discusses how to control transitions in friction...surveys classical friction theory in relation to the atomic scale...provides numerous examples and data tables for the understanding of friction through experiments...covers friction transitions, friction curve analysis, and various approaches to the graphical portrayal of friction data...reviews the practical applications for automobile engines and brakes, mechanical seals, and friction in metalworking and machining...shows how to diagnose troublesome conditions in unsteady frictional behavior, the running-in of machines, and related variability in friction...examines the frictional behavior of metals, ceramics, polymers, and other materials, including diamonds and ice...and more."--BOOK JACKET.